PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN (PKn) DENGAN METODE BERMAIN PERANDI KELAS V SDN 23 BATANG ANAIPADANG PARIAMAN - SUSANTI, YELMI (Universitas Negeri Padang, 2014)
Abstract This research aimed at describing the fifth grade students’ civics learning ouycome by using the role playing method at SDN 23 BatangAnai. The design of the research was class action research using both qualitative and quantitative approaches. The subjects of the research were the teacher and twenty fife fifth-grade students of SDN 23 BatangAnai. The result of analysis showed that the lesson plan score increased from 75% in the first meeting of cycle I to 96% in cycle II. The teacher aspect score increased from 80% in cycle I to 97% in cycle II. Meanwhile, the student score increased from 75% in cycle I to 97% in cycle II. Finally, the students’ learning outcome increased from 70% in cycle I to 82% in cycle II. Thus, the role playing method succefully improved srudents’ learning outcome. Keyword : the Role Playing Method